KONSUMSI ADF DAN NDF RANSUM TERNAK DOMBA YANG DIBERI PAKAN HIJAUAN SUPLEMEN BIJI MARKISA - Kadir, Muh. Jurhadi (Teknosains: Media Informasi Sains dan Teknologi, 2011)
This research done to know influence various level passion fruit seeds supplement (Passflora edulis) to consumption ADF and NDF supply of given by sheep livestock food in the form of greenery woof (spacious grass and bulrush). This research apply device method Latin Square (4x4), with placing four fat sheep as research livestock to four treatment ot livestock food each T0 (spacious grass + bulrush) as control, T1 (control + 50 gram passion fruit seed), T2 (control + 100 gram passion friut seed), and T3 (control + 200 gram passion friut seed). This recearch consist of four period and each period consist of five days of adjustment phase and ten days of observation phase. Observed variable is consumtion ADF and NDF supply of sheep livestock food which is mixed greenery woof and fassion fruit seed supplement. Analysis of variance result indicate that treatment have significant effect (P<0,01) to consumption ADF and have a real effect (P<0,05) to consumtion NDF. Treatment T1, T2, and T3 increase consumption of ADF and NDF than T0 (control). Consumption ADF and NDF on treatment T2 is higher than treatment (control) but on treatment there are tendency of deficiency of consumption ADF and NDF, it can be caused by reaching optimum point where requirement of energi of energi have been sufficient. Increasing of consumption ADF and NDF on extending of passion fruit seed is forecasted by palatability from passion fruit seed is better so axtending of passion fruit seed as many as 200 gram that given greenery woof can increase consumption ADF and NDF Keyword: Consumption ADF and NDF, passion fruit seed, greenery woof (spacious grass + bulrush), sheep livestock.